ANALYSIS OF THE INFLUENCE OF GREEN DIGITAL ON GREEN FINANCE IN DEVELOPED COUNTRIES IN ASIA - Rusdianto, Budi; Efendi, Bakhtiar; Rusiadi, Rusiadi; Nasution, Lia Nazliana; Suhendi, Suhendi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This research aims to see the influence of green digital on green finance in developed Asian countries, namely Japan, South Korea, Singapore and Hong Kong. Since Covid 19 hit throughout the world, digital transformation has grown very rapidly. Now transactions are made easier with the help of digital, and in developed countries digitalization and a sustainable economy are developing very rapidly. This research uses a linear regression analysis model with green finance as the dependent variable and green digital as the independent variable. The results show that green digital has an influence on green freedom in developed Asian countries.